Desenvolvimento e avaliação das atividades antioxidante e despigmentante in vitro de emulsões múltiplas a/o/a contendo dipalmitato kójico - Marcussi, Diana Gleide [UNESP] (2012)
Currently, there has been a growing concern for men and women with the appearance of the face and body, driven primarily by aesthetic standards set by the media. For this, the pharmaceutical and cosmetic industries have conducted numerous research projects aiming at the development of formulations that mitigate the aging and some skin disorders such as hipercromies. One of the most frequent pathologies of skin is melasma, a manifestation of hyperpigmentation caused by hipermelanogenesis symmetrical and progressive, caused usually by hormonal irregularities, exposure to sunlight and genetic factors. In addition to sunscreen, the treatment is indicated the use of depigmenting substances, among them the kojic dipalmitate (DK), which is cleaved into kojic acid (5- hydroxy-2-hydroxy-methyl-4H-piran-4-one) by esterase after absorption by the skin cells. The kojic acid inhibits the action of tyrosinase as a chelator of ions and promotes the reduction of eumelanin and its precursor monomer. To promote a controlled release and improve the stability of the system, the DK can be incorporated into multiple emulsions, that is, complex systems composed of two emulsifications, where the two types of emulsions (W/O and O/W or O/W and W/O) exist simultaneously, forming emulsions of type W/O/W or O/W/O. This work aimed to incorporate the DK in emulsion W/O/W, physical-chemical systems obtained and to evaluate the antioxidant and depigmenting action in vitro of the developed formulations. The physico-chemical characterization was performed by microscopic analysis, quantification and size distribution, determination of pH, conductivity, zeta potential and bioadhesive test of the formulations. The droplet size in accordance with the use of light microscopy and dynamic light scattering is approximately 1μm. The pH, electrical conductivity and bioadhesion have not changed with the addition... (Complete abstract click electronic access below)